1990
DOI: 10.1093/ageing/19.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Serum Copper Levels in Elderly Patients with Femoral-neck Fractures

Abstract: The serum copper levels of 46 elderly patients with fractures of the femoral neck were assayed and found to be significantly lower than those of a group of controls matched for age and sex. These findings are consistent with nutritional copper deficiency which may contribute to the development of fractures by reducing bone strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 0 publications
1
27
0
2
Order By: Relevance
“…In humans, there is some evidence for a role for Cu de®ciency in age-related osteoporosis. For example, Conlan et al (1990) found that serum Cu levels of 46 elderly patients with fractures of the femoral neck were signi®cantly lower than those of a group of controls matched for age and sex. A signi®cant positive correlation between serum Cu concentration and bone mineral density (BMD) at the lumbar spine has been reported in a cross-sectional study in postmenopausal women (Howard et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, there is some evidence for a role for Cu de®ciency in age-related osteoporosis. For example, Conlan et al (1990) found that serum Cu levels of 46 elderly patients with fractures of the femoral neck were signi®cantly lower than those of a group of controls matched for age and sex. A signi®cant positive correlation between serum Cu concentration and bone mineral density (BMD) at the lumbar spine has been reported in a cross-sectional study in postmenopausal women (Howard et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the demonstrated physiological rise of ceruloplasmin in arthritis is suggested to represent a protective response. Consistent with this, a lack of rise of ceruloplasmin may increase the risk of chronic disease, as seen in Cu-deficient animals with adjuvant arthritis (Conlan et al 1990). There is some evidence for a role of Cu deficiency in age-related osteroporosis.…”
Section: Discussionmentioning
confidence: 73%
“…Serum copper levels of 46 elderly patients with fractures of the femoral neck were reported to be significantly lower than those of a group of controls matched for age and sex (Jorde et al 2010). A significant positive correlation between serum Cu concentration and bone mineral density at the lumbar spine has been reported in a cross-sectional study in postmenopausal women (Conlan et al 1990). EatonEvans et al (1996) have recently shown that Cu supplementation (3 mg/day for 2 days) reduced the rate of loss of bone mineral density at the lumbar spine in 46to 56year-old women.…”
Section: Discussionmentioning
confidence: 89%
“…Hence the demonstrated physiological rise of ceruloplasmin in arthritis is suggested to repre-sent a protective response. Consistent with this, a lack of rise of ceruloplasmin may increase the risk of chronic disease, as seen in Cu-deficient animals with adjuvant arthritis (Conlan et al, 1990). There is some evidence for a role of Cu deficiency in age-related osteoporosis.…”
Section: -Discussionmentioning
confidence: 74%
“…Serum copper levels of 46 elderly patients with fractures of the femoral neck were reported to be significantly lower than those of a group of controls matched for age and sex (Jorde et al, 2010). A significant positive correlation between serum Cu concentration and bone mineral density at the lumbar spine has been reported in a cross sectional study in postmenopausal women (Conlan et al, 1990). Eaton- Evans et al(1996) have recently shown that Cu supplementation (3 mg/day for 2 days) reduced the rate of loss of bone mineral density at the lumbar spine in 46-to 56-year-old women.…”
Section: -Discussionmentioning
confidence: 89%